Effect of fatigue on spontaneous velocity variations in human middle-distance running: use of short-term Fourier transformation - Cottin, F.; Papelier, Y.; Durbin, F.; Koralsztein, J. P.; Billat, V. L. (European Journal of Applied Physiology, 2002)
Best performances in middle-distance running are characterized by coefficients of variation of the velocity ranging from 1% to 5%. This seems to suggest that running at constant velocity is a strain inducing an increase in physiological variables such as oxygen uptake. This study tested three questions. (l) Does velocity variability during a middle-distance all-out run increase with fatigue? (2) Does velocity variability alter the slow phase of the oxygen kinetic because of small spontaneous recoveries, compared with the same distance run at constant velocity? (3) Is a maintained average velocity over a given distance enhanced by a variable-pace rather than by a constant-pace? Ten long-distance runners performed two series of all-out runs over the distance (previously determined) which they could cover maintaining a velocity equal to 90% of that eliciting maximal oxygen consumption. In the first series (free-pace) the subjects were asked to run as fast as possible, without any predetermined velocity profile. In the second series, the same distance was covered at a constant velocity (equal to the average in the previous free-pace run), set by a cyclist preceding the runner. Short-term Fourier transform was used to analyse velocity oscillations. Our results show that: (1) for all subjects, the mean energy spectrum did not change throughout the free-pace runs, suggesting that velocity variability did not increase with fatigue (2-way ANOVA, P=0.557); (2) the kinetic of oxygen uptake and its asymptote were not changed during the free-pace runs compared to the constant-velocity run; (3) performance was not significantly improved by free-pace average velocity [mean (SD) 4.22 (0.47) compared to 4.25 (0.52) m·s-1 for constant and free-pace respectively, t=-0.58, P=0.57]. These results indicate that during middle-distance running, fatigue does not increase variations in velocity, and free-pace changes neither performance nor the oxygen kinetic.